Shariah Governance and Financing Risk in Islamic Banks: A Conceptual Analysis - Fuad, Yahya (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study aims to explore the role of Shariah governance in minimizing financing risk in Islamic banking by focusing on the functions of the Shariah Supervisory Board (SSB) and Internal Shariah Review (ISR). The research synthesizes findings from two scholarly articles using a conceptual and qualitative analytical approach. The first article adopts a systematic literature review to identify key indicators in Shariah governance that influence credit risk, such as the qualifications of SSB members and the effectiveness of ISR. The second article utilizes Erving Goffman’s frame analysis to understand how interactions between bank managers and SSB members may impact Shariah compliance in practice. The analysis reveals that a well-functioning SSB and ISR significantly contribute to reducing financing risk by ensuring that banking operations align with Shariah principles. Furthermore, managerial strategies, such as impression management, may influence the decisions of Shariah boards, raising concerns about the consistency and integrity of compliance mechanisms. These findings highlight the dual importance of institutional competency and ethical governance in mitigating risk and maintaining public trust in Islamic financial institutions. In conclusion, the study emphasizes the need for capacity building in Shariah governance structures, particularly in enhancing the qualifications and independence of SSB members and strengthening internal Shariah review functions. Future research is encouraged to further examine the effectiveness of ISR across various financial products and jurisdictions, and to explore how governance practices affect credit ratings in Islamic banking